A two-component response regulator is involved in cold sensing in oat - Zakhrabekova, Shakhira; Bräutigam, Marcus; Olsson, Olof (MTT, 2004)
Plants have developed a number of different physiological and developmental responses to abiotic stress. One important process is acclimation, where mild stress conditions greatly enhance tolerance to later and more severe conditions. During the acclimation changes in gene expression patterns occur, which leads to a plant response involving the necessary modifications of growth, development and cellular homeostasis. During the last years, six different cellular signal transduction pathways between the initial cold-stress perception and the gene expression response have been documented. Here we suggest an additional pathway. Two component systems, first described in prokaryotes, have also been identified in yeast and plant systems, but not in animals. They are characterised by a phosphotransfer reaction between two types of signal transducers and involves a sensory histidine kinase receptor and a response regulator. In plants, two-component systems play important roles in ethylene and cytokinin signalling and osmosensing but have not been directly coupled to cold signalling so far. From a subtractive oat cDNA library enriched in cold induced sequences we isolated a full-length clone, denoted AsDP5. Northern and RT-PCR analysis showed that the AsDP5 was induced at +4oC in less than 1 h. Analysis of the deduced 621 amino acids long protein revealed that it had a N-terminal two component response regulator domain, putative nuclear localisation signals and a zink finger DNA binding domain at the C-terminus. Thus, the AsDP5 protein strongly resembles the response regulator protein of two-component systems. This cold signalling pathway is now carefully analysed in oat and in the model plant Arabidopsis, using various knock-out mutants and transgenic systems.
Keywords: Ka; two component systems; response regulator; cold induction